Subantarctic pCO2 estimated from a biogeochemical float: comparison with moored observations reinforces the importance of spatial and temporal variability - Wynn-Edwards, Cathryn Ann; Shadwick, Elizabeth H.; Jansen, Peter; Schallenberg, Christina; Maurer, Tanya Lea; Sutton, Adrienne J. (Frontiers in Marine Science, 2023)
Understanding the size and future changes of natural ocean carbon sinks is critical for the projection of atmospheric CO2 levels. The magnitude of the Southern Ocean carbon flux has varied significantly over past decades but mechanisms behind this variability are still under debate. While high accuracy observations, e.g. from ships and moored platforms, are important to improve models they are limited through space and time. Observations from autonomous platforms with emerging biogeochemical capabilities, e.g. profiling floats, provide greater spatial and temporal coverage. However, the absolute accuracy of CO2 partial pressure (pCO2) derived from float pH sensors is not well constrained. Here we capitalize on data collected for over a year by a biogeochemical Argo float near the Southern Ocean Time Series observatory to evaluate the accuracy of pCO2 estimates from floats beyond the initial in water comparisons at deployment. A latitudinal gradient of increasing pCO2 southward and spatial variability contributed to observed discrepancies. Comparisons between float estimated pCO2 and mooring observations were therefore restricted by temperature and potential density criteria ( 7 µatm difference) and distance (1° latitude and longitude, 11 µatm difference). By utilizing high quality moored and shipboard underway pCO2 observations, and estimates from CTD casts, we therefore found that over a year, differences in pCO2 between platforms were within tolerable uncertainties. Continued validation efforts, using measurements with known and sufficient accuracy, are vital in the continued assessment of float-based pCO2 estimates, especially in a highly dynamic region such as the subantarctic zone of the Southern Ocean.